The Evidence-Base for Psychodynamic Psychotherapy With Children and Adolescents: A Narrative Synthesis - Midgley, Nick; Mortimer, Rose; Cirasola, Antonella; Batra, Prisha; Kennedy, Eilis (Frontiers in Psychology, 2021)
Despite a rich theoretical and clinical history, psychodynamic child psychotherapy has been slow to engage in the empirical assessment of its effectiveness. This systematic review aims to provide a narrative synthesis of the evidence base for psychodynamic therapy with children and adolescents. Building on two earlier systematic reviews, which covered the period up to 2017, the current study involved two stages: an updated literature search, covering the period between January 2017 and May 2020, and a narrative synthesis of these new studies with those identified in the earlier reviews. The updated search identified 37 papers (28 distinct studies). When combined with papers identified in the earlier systematic reviews, this resulted in a combined total of 123 papers (82 distinct studies). The narrative synthesis of findings indicates that there is evidence of effectiveness for psychodynamic therapy in treating a wide range of mental health difficulties in children and adolescents. The evidence suggests this approach may be especially effective for internalizing disorders such as depression and anxiety, as well as in the treatment of emerging personality disorders and in the treatment of children who have experience of adversity. Both the quality and quantity of empirical papers in this field has increased over time. However, much of the research demonstrates a range of methodological limitations (small sample sizes, lack of control groups etc.), and only 22 studies were Randomized Controlled Trials. Further high-quality research is needed in order to better understand the effectiveness of psychodynamic psychotherapy for children and young people.